THE INFLUENCE OF SELF-EFFICACY AND JOB STRESS TOWARD JOB BURNOUT AT A PACKAGING COMPANY IN SURABAYA - Hayyu Fathil Hasanah; Noeroel Widajati; Indriati Paskarini; Tri Martiana; Aisy Rahmania (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Job burnout is a phenomenon that often occurs in the workplace because of experiencing prolonged job stress. The higher the level of workers' self-efficacy, the lower the probability of job stress and the potential of job burnout experienced by workers. Purpose: To identify the influence of self-efficacy and job stress toward job burnout at a packaging company in Surabaya. Method: It was an analytical observational research with a cross-sectional approach. The respondents of this research were 99 workers in the production site of the packaging company in Surabaya. Questionnaire was used to collect individual data including age, gender, work period, education, and marital status which were related to the respondents' characteristics, while self-efficacy questionnaire was used to gather data about the workers' self-efficacy, HSE Management Standards Indicator Tool for job stress questionnaire, and Maslach Burnout Inventory (MBI) for job burnout questionnaire. Further, simple random sampling was used to draw the sample. The data were descriptively analyzed using related linear regression test. Result: Self-efficacy was proved to significantly influence job burnout in the aspects of reduced personal accomplishment (p-value=0.000), but self-efficacy did not influence job burnout in the aspects of emotional exhaustion and depersonalization. Whereas job stress was proved to significantly influence job burnout in the aspect of emotional exhaustion, depersonalization or reduced personal accomplishment (p-value=0.000). Conclusion: In sum, all aspects in job burnout were influenced by job stress.